Algal Diversity in the Rice Field of Parsa District (Nepal) - Bala, Kiran; Sinha, Anil Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Twenty two species of algae were collected from rice field of Parsa district, Nepal and identified and recorded. Three Chlorophyceae, ten heterocystous cyanophceae and nine non-heterocystous cyanophyceae. Oscillatoria was most common in all the three selected rice field. Other species like Nostoc linkia, Anabaena oryzae and Merismopedia elegans have been also found as dominant taxa. Six cyanophyta and two chlorophyta are newly reported for Nepal.